Expanding the role of teacher leaders: Professional learning for policy advocacy - Mary Lynne Derrington; Lezli S. Anderson (Arizona State University, 2020)
Teacher leadership is important both within and beyond the school. Teacher leaders have the potential to expand their role beyond policy implementation in the classroom to influence educational policy development. However, few teachers receive explicit preparation or guidance for contributing their voice and providing first-hand knowledge of policy's classroom impact. This study investigated the perceptions and experiences of educators who had completed a year-long fellowship designed to inform and guide teacher participation in state policy. The results indicate that participants perceive themselves as strong policy advocates with local stakeholders but believe they face barriers to influencing state policy leaders. The findings suggest that (1) barriers to policy advocacy must be examined and removed so that teachers can expand their expertise beyond the classroom and that (2) professional learning opportunities can develop teacher leadership skills for influencing policy formulation and adoption resulting in benefits for students.